IDENTIFICATION OF RISK FACTORS FOR SELECTED NON COMMUNICABLE DISEASES AMONG PUBLIC SECTOR OFFICE EMPLOYEES, SRI LANKA - Swarnamali, A K S H; Jayasinghe, M V T N; Katulanda, P (LIFE: International Journal of Health and Life-Sciences, 2015)
The increasing prevalence of Non communicable diseases has been observed in many low income countries during the last decades. Occupational health plays a major role as it is the stem of the country. Documented scientific proven quantity and quality based descriptive evidence on the nutritional, physical activity and other risk factors among office employees are lacking in Sri Lanka. A descriptive cross sectional study was conducted with 380 public sector office employees in Sri Lanka. Socio demographic and behavioral risk factor data (smoking, alcoholism)- using self-administered questionnaire, anthropometry data (weigh, height, waist and hip circumference), blood pressure dietary data using semi quantitative Food Frequency Questionnaire, Physical activity data using International Physical Activity Questionnaire - long form and fasting blood glucose level were assessed. Data was analyzed using SPSS version 16. Mean age of the study population was 38 years (± 9.22). There 38.7% were obese and 20.6% were overweight. Mean waist circumference was 86.75 (± 9.83) cm. 55.2% of them were centrally obese, average waist to hip ratio was 0.92 (± 0.07) and 62.1% of them were having higher waist to hip ratio according to the WHO (Asian) cut off. 39.9% population was under the pre-hypertensive stage. There 4.8% were diabetes and 7.7% were pre-diabetes. 17.2% of male were currently smoking and 52.6% of male were using alcohol. There 31% were inactive while majority of them (61.7%) were moderately physically active. Median Total PA score was 963 MET-min/weeks. Highest PA score was at Domestic and garden domain (420 MET-min/week), and lowest PA score was at work domain (33 MET-min/week). Daily intake of fruit, vegetable and dairy foods were well below national recommendations. Overweight, obesity, central obesity and pre-hypertension, unhealthy eating habits and sedentary during working were identified as risk factors.